Barriers Interfere With Wide Usage of NOAC for Prevention of Thromboembolic Events Among Doctors in Sudan: A Cross-Sectional Survey February 2023 - Elaf Sabri Khalil; Asmaa Elfatih Hussein Omer; Wadaha Mohamed Nouh Mohamed; Mustafa Sabir Abakar Awad (Cardiology Research and Practice)
Conclusion: Sudanese clinicians’ hurdles to using NOAC for thromboembolic episodes were explored. Lack of a reversal agent and multidisciplinary team approach hinder DOAC prescription. Lack of information about international guidelines, since most participant’s preferred specialized advice or personal experience, and high DOAC costs and inaccessibility and unavailability are other important barriers. Medical practitioners should update guidelines and government insurance plans should include DOACs. Each department should start studies separately.